System Instrumentation and Modeling of Power and Energy Demand for Tillage Operations in Malaysia - Kheiralla, Abdelmotalab Fadlelmola (2002)
Malaysia stands as a world's pertinent producer of palm oil, rubber and cocoa. An increase in food imports coupled with limited agricultural workers have driven the need for the development of integrated system for agriculture database to manage the country's limited resources. The development of a database on power and energy demand of various agricultural field operations is a prime concern for an economical management of input resources for agricultural production. A complete tractor instrumentation and data acquisition system was developed and installed on a Massey Ferguson 3060 agricultural tractor for power and energy demand mapping of the agricultural field operations in Malaysia. The built-in instrumentation system is able to measure and display infonnation on engine speed, PTO speed, forward speed, drive wheel slippage, acres worked, fuel consumption per hour, fuel consumption per hectare, flied capacity, cost factor, fuel consumed, fuel remaining, and distance. The developed data acquisition system is able to measure and monitor horizontal pull at the tractor drawbar point, torques at both tractor rear drive wheels, torque at the tractor PTO output, and the horizontal and vertical forces on the implement at the 3-point hitch. Static calibration tests on all the designed transducers for the required measurements showed excellent linearity (i.e., correlation coefficients closed to 0.99). The field trials demonstrated that the datalogger and associated transducers were able to function successfully without giving problems under the harsh field environments. The stored data in the memory card of the datalogger from the field trials was able to be down loaded into the hard disk of the host computer at the laboratory for post processing.